Intestinal endometriosis treated by laparoscopic surgery: case series of 5 patients - Hiroka Kondo; Yasumitsu Hirano; Toshimasa Ishii; Kiyoka Hara; Nao Obara; Liming Wang; Masahiro Asari; Takuya Kato; Shigeki Yamaguchi (Surgical Case Reports, 2020)
Abstract Background Intestinal endometriosis is rare and most frequently involves the rectum and sigmoid colon. Case presentation Here, we report a case series of 5 patients who underwent laparoscopic resection for intestinal endometriosis. None of the patients developed postoperative complications, and all were discharged at 5–8 days after surgery. The diagnosis of intestinal endometriosis is difficult to obtain before surgery. Only 2 of 5 patients were diagnosed preoperatively. Among 1 of the 2 patients, the symptoms at the time of menstruation were obvious. In patients with submucosal tumors, the preoperative diagnosis can be difficult. Additional imaging examinations at the time of menstruation might be useful for obtaining a diagnosis. D2 dissections were performed for 3 patients, because malignancy could not be ruled out as a preoperative diagnosis. The surgical findings of 1 patient did not appear to be endometriosis. Surgery for intestinal endometriosis usually encounters advanced pelvic adhesions and fibrosis. For patients undergoing sigmoidectomy, the mean operative time was 152 min and mean blood loss was 10 mL. For patients undergoing rectal resection, the mean operative time was 282 min and mean blood loss was 17 mL. Two cases had severe pelvic adhesions, and the residual rectum could not be straightened. Therefore, side-to-side anastomosis was performed. For intestinal endometriosis surgery, flexible planning for the anastomosis method used for residual intestine should be undertaken. Conclusion Laparoscopic surgery for intestinal endometriosis was safe but technically difficult, because of fibrosis and adhesions. An accurate diagnosis should be attempted based on the clinical symptoms, imaging findings, and intraoperative findings. The method used for anastomosis should be decided on a case-by-case basis.